Influence of adaptation on human thermal comfort in outdoor areas of Malaysia - Makaremi, Nastaran; Salleh, Elias; GhaffarianHoseini, AmirHosein (2011)
Basically, outdoor spaces are perceived as the integral constituent of urban design developments in order to provide the opportunities for recreational activities. Thereby, thermal comfort of outdoor spaces is one of the substantial issues which must be highly considered within their design process. Nevertheless, the human responses to the outdoor environment and actual thermal sensation experienced by individuals as subjective human parameters have not been fully investigated in outdoor thermal comfort studies. Accordingly, this study intends to concentrate on the human thermal comfort conditions of outdoor environments in hot and humid tropical climate as the main focus of this research. This paper compares available assessments of outdoor thermal comfort to explain the differences between the tolerances of people of different regions. The findings of thermal comfort investigations could be applied into improving the quality of urban areas in order to increase the outdoor activities of citizens and use of outdoor spaces in hot and humid countries. The study contributes towards understanding the circumstances of creating thermally comfortable environments to develop a widespread climatic criterion for human comfort in outdoor urban areas.